2014
DOI: 10.2174/1389201015666140330192941
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Substance P on the Pathogenesis of Insulin Resistance Leading to Gestational Diabetes

Abstract: Gestational diabetes mellitus is one of the most often medical conditions during pregnancy affecting 5-6% of all pregnancies. The etiology of gestational diabetes is not clearly understood. In obesity and diabetes mellitus type 2, abnormal insulin signaling is an important agent mediating the increase of insulin resistance. Insulin receptor substrate serine phosphorylation is a time-controlled physiological reaction in insulin signaling that has been disrupted by metabolic and inflammatory stresses to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Gestational diabetes mellitus (GDM) is a heterogeneous pathogenic condition affecting 2-5% of all pregnant women during pregnancy [223,224] in other data is 5-6% [225]. GDM and T2DM share a common pathophysiological background, including β-cell dysfunction and IR [226,227].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) is a heterogeneous pathogenic condition affecting 2-5% of all pregnant women during pregnancy [223,224] in other data is 5-6% [225]. GDM and T2DM share a common pathophysiological background, including β-cell dysfunction and IR [226,227].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…The stimulators or the inducers of IR and phosphorylate insulin receptor substrate (IRS) proteins are activated in uncontrollable method several kinases, including inhibitor of nuclear factor ĸB kinase β (IKK β), c-Jun N-terminal kinase (JNK), mammalian target of rapamycin (mTOR), protein kinase C (PKC) and ribosomal S6 protein kinase (S6K). Substance P is a potent cytokine and is considered one of the crucial activators that contribute in the development of IR by impairment of insulin signaling [225]. The genetic variants in TCF7L2 is the strongest gene associated with GDM risk among other minor alleles of rs7903146 (TCF7L2), rs1225 5372 (TCF7L2), rs1799884 (-30G/A, GCK), rs5219 (E23K, KCNJ11), rs7754840 (CDKAL1), rs4402960 (IGF2BP2), rs10830963 (MTNR1B), rs1387153 (MTNR1B) and rs1801278 (Gly972Arg, IRS1) significantly associated with a higher risk of GDM.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Gestational diabetes is one kind of common diseases which affects 5 to 6% of pregnant women [24]. There are some predicting associations which shows top 10 predicted metabolites and 9 of top 10 predicted Gestational diabetes-related metabolites have been certified (see Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…There are some predicting associations which shows top 10 predicted metabolites and 9 of top 10 predicted Gestational diabetes-related metabolites have been certified (see Table 5). More and more details indicated that the Substance might be a new role which lead not only to the development of diabetes gestational diabetes, but also diabetes mellitus type 2 [24]. Although there is no clear evidence to confirm the associations between Guanidoacetic acid and Gestational diabetes, some experimental literatures show that the detection of Guanidoacetic acid is an available indicator for renal tubular dysfunction in the early phase of diabetes mellitus [25].…”
Section: Resultsmentioning
confidence: 99%
“…Increased SP levels occur with obesity and diabetes in human SP and in mouse models (for review, see ref. 42). NK1R-KO mice are more resistant to the development of obesity (43); similar effects were observed using NK1R antagonists (44).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%